Interactions between sleep habits and self-control - Pilcher, June J.; Morris, Drew M.; Donnelly, Janet; Feigl, Hayley B. (Frontiers in Human Neuroscience, 2015)
Good sleep habits and effective self-control are important components of successful functioning. Unfortunately chronic sleep loss and impaired self-control are common occurrences for many individuals which can lead to difficulty with daily self-control issues such as resisting impulses and maintaining attentive behavior. Understanding how self-control is depleted and how good sleep habits may help replenish and maintain the capacity for self-control is an important issue. A sleep-deprived individual who has expended the necessary resources for self-control is at an increased risk for succumbing to impulsive desires, poor attentional capacity, and compromised decision making. To date, few studies have investigated how sleep and self-control are inter-related. The goal of this mini-review is to explore the intersection between sleep habits and self-control and encourage researchers to focus on a new area of research that integrates what are at present largely separate areas in psychology and human neurosciences.